Belief, language, and experience - Needham, Rodney (Basil Blackwell, 1972)
A sophisticated philosophical inquiry into the problem of whether “belief” is a property of individual minds or a collective dogma to which everybody mindlessly subscribes. Belief is not a discriminable experience, it does not constitute a natural resemblance among men, and it does not belong to the common behavior of mankind.
free
Keywords: Wittgenstein; Ludwig; 1889-1951